Optimization of Investigations by the PPA Unit in Handling Violence Cases by Children to Enforce Justice Law in Tegal Polres (Advances in Police Science Research Journal, 2024)
Fighting action is a form of violence perpetrated by children. The handling of children who are in conflict with the law is of course different from the handling of criminal acts committed by adults. The rise of brawls that occurred in Tegal Regency made the PPA Satreskrim Unit of the Tegal Police determined to reduce the number of brawls that occurred by carrying out investigations and efforts to enforce the law fairly through diversion for children who violated it. This writing aims to describe the operational management of the Tegal Police PPA Unit in carrying out investigations and to describe the implementation of diversion as an effort to uphold justice in the Tegal Police in handling cases of violence by children. The research was conducted using a qualitative approach and data collection techniques through observation, interviews and document review. In chapter II of contextual literature, the author uses SWOT theory as a knife for analyzing influencing factors, as well as management theory and law enforcement theory to discuss the concept of optimization, the concept of settlement, the concept of children, the concept of diversion to analyze the problem formulation in chapter I. The results of the research in this final project are that the PPA Unit's investigation efforts in handling cases of violence by children have been carried out, but there are still some deficiencies, starting from planning because there is no activity planning, organizing due to lack of personnel, imbalance in the division of tasks and infrastructure, actuating because in In the implementation of summons, examinations, arrests and detentions, there were still some deficiencies and errors in the controlling process because all investigators did not attend the trial with unclear absence statements. Based on the author's observations, the PPA Satreskrim Polres Tegal Unit must evaluate the implementation of the investigation from the initial summons to the diversion stage in the investigation as a settlement of cases of violence by children in order to enforce a just law at the Tegal Police.
Keywords: Kekerasan dengan pelaku anak; Penyidikan